Nigella Sativa Seed Extract has Potential Antimicrobial Activity on Pasteurella multocida in Vitro - Vanda, Henni; Zakya Ardi; Sari, Wahyu Eka; Hambal, Muhammad (IPB University, 2023)
Nigella sativa known as black cumin has various bioactive compounds to treat many diseases. Some of the benefits of N. sativa seed are as immune booster, antihistamin, anti-diabetic, antihypertension, antiinflammatory, antimicrobial, and antitumor. This study aimed at determining the antimicrobial activity and finding out the effective concentration of N. sativa seed ethanolic extract on Pasteurella multocida in vitro. N. sativa seed extract was divided into three groups consisting of 15% extract (T1), 25% extract (T2), 45% extract (T3), and chloramphenicol was used as positive control. For antimicrobial test, Kirby Bauer diffusion method was used, and the data were analyzed by ANOVA. The results revealed that T3 had the most effective antimicrobial activity, shown by the largest inhibition zone (17.72 mm), followed by T2 (15.93 mm) and T1 (10.75 mm). ANOVA test results showed significant differences (P<0.05) in each group. The antimicrobial effect of T3 and T2 was categorized as strong, whilst T1 as moderate. From the results it can be concluded that N. sativa seed extract had strong and moderate inhibition activity on the growth of P. multocida, therefore, N. sativa seed is a potential candidate for antimicrobial drug development againts P. multocida.